PERANAN PEMERINTAHAN NAGARI DALAM PELAKSANAAN PEMBANGUNAN DI KENAGARIAN GUGUAK VIII KOTO KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Putri, Dwiana; Tinov, Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background of this research was by the rise of local regulations number 10 in 2007 about nagari government that caused all the lowest Government is changed to be nagari government. In the local regulations stated that nagari government have obligation to build their district. To man tain the development that will be carried out, the nagari government of Guguak VIII koto provided planning discussion for development. But in fact, development was still far from the target on Nagari development planning.Therefore, in this research the formulations of the problem is that how duty’s implementation, authority and obligation of nagari Government in implemanting the development in Kenagarian Guguak VIII Koto in 2012 are. The purpose of this research was to find out the role of Nagari Government members in implementing the development in Kenagarian Guguak VIII Koto, and also to find out the reasons why the development was still far from the target on Nagari Development’s planning in 2012.The method of this research was qualitatif method that analyzed the data as descriptif analysis. In collecting data, the writer used interview, questionnaire, literature review and documentation. The data resources used was primary data got in research’s location and secondary data (Documentation).In this research, the responden used by writer was Wali Nagari, Secretary of Nagari, the head of development, the head of government, the head of financial, staff public relations of nagari and Wali Jorong. From the research findings of the respondents can be argued that the governments payed little attention to the implementation of development. It was proven from the very rarity of government official conducted a review to the construction site. Besides, the financial factor was also a major caused of delays in construction of Kenagarian Guguak.Key Words : Development, Nagari Government, Kenagarian Guguak VIII Koto